PELAKSANAAN PENGHITUNGAN PENYETORAN DAN PELAPORAN PAJAK PENGHASILAN PASAL 26 ATAS ROYALTI MASA PAJAK JANUARI SAMPAI DENGAN DESEMBER 2015 PADA PT ATLAS COPCO INDONESIA - Edy Edy; Devi Purnama Sari; Andini Apriyanti (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2016)
PT Atlas Copco Indonesia is a company with heavy machinery and other equipment as products and its business activities often associated with foreign tax subject (SPLN), one of the most transaction applied is royalty payments which in this case is the object of the tax role in withholding tax Article 26. PT Atlas Copco Indonesia did start counting taxation liabilities of deposit and report the Income Tax Article 26. In Chapter II, the writer suggested the definition of income tax related to taxes definistion, tax functions, types of taxes, tax collection system, Subject and Object of Income Tax 26, tax rates, and double taxation avoidance agreement (P3B or tax treaty). This final project is about an overview of the company which is PT Atlas Copco Indonesia, the implementation process of the calculation of income tax deposit and reporting Article 26. From the results of the observations made, it can be conclude that the implementation of Tax Liability from period of January to December 2015 at PT Atlas Copco Indonesia is not in accordance with the applicable Tax Regulation.